To Believe is to Know that You Believe. (September 2016) - Marcus, Eric
Abstract: Most agree that believing a proposition normally or ideally results in believing that one believes it, at least if one considers the question of whether one believes it. I defend a much stronger thesis. It is impossible to believe without knowledge of one's belief. I argue, roughly, as follows. Believing that p entails that one is able to honestly assert that p. But anyone who is able to honestly assert that p is also able to just say – i.e., authoritatively, yet not on the basis of evidence – that she believes that p. And anyone who is able to just say that she believes that p is able to act in light of the fact that she holds that belief. This ability to act, in turn, constitutes knowledge of the psychological fact. However, without a broader theory of belief to help us make sense of this result, this conclusion will be hard to accept. Why should being in a particular mental state by itself necessitate an awareness of being in that state? I sketch a theory that helps to answer this question: believing is a matter of viewing a proposition as what one ought to believe. I show how this theory explains (and entails) the thesis that to believe is to know that you believe.